Review Study on the Effect of Knotted and Knotless Knot based on Strength Properties of the Fishing Nets - Januar, Jan Eldear; Kunchi Mon, Siti Zaharah (Progress in Engineering Application and Technology, 2021)
Fishing nets are regarded as the most critical component in fishing gear yet a common problem still occurs where fracturing during hauling overweighted fishes to the ships. This paper reviews the effect of the knotted and knotless knots on strength properties of the fishing nets based on the previous studies of the current knowledge and point out areas for further research. The methods to gain the finding of the review consist of two steps; (i) identifying the literature study and (ii) mapping the content of the selected study. Based on previous research, the Angle of Attack (AOA) of knots can decrease the Drag Coefficient (Dc) and Reynolds Number (Rm) during hydrodynamic force flow into the netting panels in a uniform velocity of the water. To summarize knotted knot has a higher drag coefficient than the knotless knot where the hydrodynamic coefficient of knotless nettings was the same solidity ratio as knotted netting.